Phage display-identified PD-L1-binding peptides reinvigorate T-cell activity and inhibit tumor progression. (July 2020) - Gurung, Smriti; Khan, Fatima; Gunassekaran, Gowri Rangaswamy; Yoo, Jae Do; Poongkavithai Vadevoo, Sri Murugan; Permpoon, Uttapol; Kim, Sang-Hyun; Kim, Ha-Jeong; Kim, In-San; Han, Hyeonjeong; Park, Ji-Ho; Kim, Soyoun; et al.
Abstract: Blockade of programmed cell death ligand-1 (PD-L1) restores T-cell activity and enhances anti-tumor immunity. Screening a phage-displayed peptide library for peptides that selectively bind to PD-L1-overexpressing cells identified two peptides, CLQKTPKQC and CVRARTR (PD-L1Pep-1 and PD-L1Pep-2, respectively) that appeared to block PD-L1. PD-L1Pep-1 and PD-L1Pep-2 preferentially bound to high PD-L1-expressing cells over low PD-L1-expressing cells; binding was further enhanced by interferon-γ, an inducer of PD-L1 expression. Binding affinities of PD-L1Pep-1 and PD-L1Pep-2 were approximately 373 and 281 nM, respectively. Cellular binding of the PD-L1-binding peptides was reduced by silencing PD-L1 gene expression or competition with anti-PD-L1 antibody. PD-L1Pep-1 and PD-L1Pep-2 induced the internalization and downregulated cell surface levels of PD-L1. The PD-L1-binding peptides restored cytokine secretion and T-cell proliferation to cells inhibited by co-culture with tumor cells or culture on PD-L1-coated plates. Intravenously injected PD-L1Pep-1 and PD-L1Pep-2 efficiently homed to tumor tissues, inhibited tumor growth, and increased CD8+/FoxP3+ ratio in mice. The PD-L1-binding peptides in combination with doxorubicin or PD-L1-targeted liposomal doxorubicin inhibited tumor growth and increased CD8+/FoxP3+ ratio more efficiently than doxorubicin alone and untargeted liposomal doxorubicin, respectively. These results suggest that PD-L1Pep-1 and PD-L1Pep-2 block PD-L1 and reinvigorate T-cell activity, inhibiting tumor growth by enhancing anti-tumor immunity. Graphical abstract: Image 1